Comparison of nitrogen transformation dynamics in non-irradiated and irradiated alfalfa and red clover during ensiling - Dong, Zhihao (Asian-Australasian journal of animal sciences, 2019)
Objective: To study the contribution of plant enzyme and microbial activities on protein degradation in silage, this study evaluated the nitrogen transformation dynamics during ensiling of non- and irradiated alfalfa (Medicago sativa L.) and red clover (Trifolium pratense L.)